Carrying capacity factors influencing visitors' experience in the Giant Panda Conservation Centre, Zoo Negara, Malaysia - Law, Kar Men (2016)
Giant Panda Conservation Centre (GPCC), Zoo Negara, Malaysia was built at a cost of RM25 million and completed in April 2014 with world class facilities. After the birth of the panda cub, the number of people visit to GPCC is getting higher. In order to continue provide good experience for the visitors, carrying capacity factors that influence visitors’ experience should be determined because there is no carrying capacity research had been done in GPCC before. Without this study, management unable to do a higher research on carrying capacity in GPCC. The purpose of this study is to explore the carrying capacity factors that influence visitor experience. This research was using face-to-face questionnaire survey with 250 respondents. Results from the study show that almost all the respondents are still satisfied with facilities and environment provided in GPCC. The visitors were most satisfied with the cleanliness in waiting area and most dissatisfied with the adequacy of space in the zoovenir. The age, marital status of the visitors, physical and social carrying capacity in GPCC, and the type of visit information sources which are television or radio, Internet and brochures have been identified as the factors that influence visitors’ experience at GPCC. GPCC management should take effective planning to preserve and improve the current condition of the physical assets in GPCC.